Design and performance analysis of a voltage inverter using intelligent controllers (MASKAY, 2013)
This document describes the development of intelligent controllers to suppress harmonics in single-phase inverters with sine pulse width modulation (SPWM). In the first phase, a PI controller was designed to serve as a reference model to obtain the training patterns of the neural network. Subsequently, a fuzzy logic PD controller was designed using a base of 25 rules. Simulations carried out with the mathematical model of the inverter and using "SimPowerSystems" of MATLAB indicate that it is possible to obtain a pure sine wave with a minimum of total harmonic distortion (THD) by using the proposed intelligent controllers.
Keywords: Power Electronics; voltage inverter; harmonic distortion; THD; neural network; fuzzy logic control